Hukum Perwalian Anak Zina dan Hak Warisnya - Iman Jauhari (Universitas Syiah Kuala, 2011)
ABSTRACT: The review in this paper is to discuss the cause of the child out of wedlock, understanding and the status of illegitimate children, inheritance law of children out of wedlock and custody of the child of adultery under Islamic Law Compilation method used was content analysis (content analysis) of references relevant to the problem discussed. The legal consequences for the child out of wedlock under Islamic Law Compilation is a child born outside marriage has only nasab relationship with her mother and her family alone, so it legally, the child can not be completely attributed to the father father nature, although the real father/natural father (genetic) are the men who impregnate women who gave birth to her it. Thus a child outside of marriage guardian is the guardian of judges who have been appointed by the government. Legal Guardianship of Adultery Child and the Right of Their Inheritence